Effect of TikTok Usage on the Moral Development of University Students - Dr. Shamaiela Farooqi; Dr. Shafqat Rasool; Asma Ishtiaq (Dialogue Social Science Review (DSSR), 2025)
This study explores how TikTok usage affects university students' moral development. Data were gathered via a questionnaire from 400 students across public and private universities in Faisalabad, Pakistan. The main objectives were to assess the level of TikTok use, moral development. SPSS version 21 was used for analysis, employing descriptive statistics, independent sample t-tests, one-way ANOVA, and regression. The study found significant levels of moral development, Coefficient results indicated that TikTok and moral development have an inverse relationship. Regression results indicated that when level of use of TikTok increases by one unit moral development decreases by 0.62 units.